Proceedings (88) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
National online meeting is the proceedings of a meeting held from 13-15 May 1997, New York, USA edited by Martha E Williams - ISBN 1 57387 043 9Information Today Inc. 143 Old Marlton Pike, Medford, NJ 08055, USA